Backlog and burden of fractures in Sierra Leone and Nepal: Results from nationwide cluster randomized, population-based surveys. (September 2016) - Stewart, Barclay T.; Kushner, Adam L.; Kamara, Thaim B.; Shrestha, Sunil; Gupta, Shailvi; Groen, Reinou S.; Nwomeh, Ben; Gosselin, Richard A.; Spiegel, David
Abstract: Background: The burden of injury is increasing worldwide; planning for its impact on population health and health systems is urgently needed, particularly in low- and middle-income countries (LMICs). This study aimed to model the burden of fractures and project costs to eliminate avertable fracture-related disability-adjusted life-years (i.e., a measure of overall disease burden, expressed as the number of years lost due to ill-health, disability or premature death; DALYs) in Sierra Leone and Nepal. Methods: Data from nationwide, cluster-randomized, community-based surveys of surgical need in Sierra Leone and Nepal were used to model the incidence and prevalence of fractures stratified by met and unmet needs. DALYs incurred from treated and untreated fractures were estimated. Additionally, the investment necessary to eliminate avertable incident fracture DALYs was modeled through 2025 using published cost per DALY averted estimates. Results: The incidence of treated and untreated fractures in Sierra Leone was 570 and 1004 fractures per 100, 000 persons, respectively. There could be more than 2 million avertable fracture DALYs by 2025 in Sierra Leone and 2.5 million in Nepal requiring an estimated US$ 4, 049, 932 (range US$ 2, 011, 500–6, 088, 364) and US$ 4, 962, 402 (range US$ 2, 464, 701–7, 460, 103) to address this excess burden, respectively. Conclusion: This study identified a significant burden of untreated fractures in both countries, and an opportunity to avert more than 4.5 million DALYs in 10 years in a cost-effective manner. Prioritizing funding mechanisms for orthopaedic care and implants should be considered given the large burden of untreated fractures found in both countries and the long-term savings and functional benefit from properly treated fractures. Highlights: More than 2 million DALYs incurred by fractures could be averted by 2025 in Sierra Leone and 2.5 million DALYs could be averted in Nepal. Averting the aforementioned DALYs will require an estimated US$ 4, 049, 932 (range US$ 2, 011, 500–6, 088, 364) and US$ 4, 962, 402 (range US$ 2, 464, 701–7, 460, 103), respectively.